Reasonable Support Parameters for Loess Tunnel Under Different Water Contents: A Case Study - Hao Chen; Yanbin Luo; Jianxun Chen; Hui Chen; Yanfeng Li; Pengkun Wang; Lele Guo (Applied Sciences)
Due to the unique structural characteristics of loess, the strength of loess is significantly influenced by the water content. Therefore, different support parameters should be used for loess tunnels constructed in different water content strata. This paper takes the Fengshouling Tunnel as a case study, studying the reasonable primary support parameters under different water contents using the surrounding rock strength test, on-site monitoring, and numerical simulation software analysis. The research findings indicate that the strength of the surrounding rock is functionally related to its water content, with the cohesive force c exhibiting an exponential relationship and the angle of internal friction φ showing a linear relationship, and that the cohesive force c is more affected by changes in water content than the internal friction angle φ. The crown settlement of the loess tunnel exceeds the horizontal convergence, and the deformation behavior can be categorized into three distinct stages: rapid growth, continuous growth, and slow growth. Concurrently, the primary support structure mainly bears compressive stress. On the basis of considering structural safety and engineering economy, for tunnels with a general water content (10~17%), it is recommended to use I18 steel ribs spaced 60 cm apart and C25 shotcrete with a 24 cm thickness; for high water content (17~25%), it is recommended to use I20a steel ribs, also spaced 60 cm apart, complemented by C25 shotcrete increased to a 26 cm thickness; for situations with an extremely high water content (≥25%), it is recommended to reinforce the surrounding rock with curtain grouting and use steel ribs with the same 60 cm spacing, along with C25 shotcrete maintained at a 26 cm thickness. This paper proposes reasonable support parameters for loess tunnels applicable to different water contents. These results can provide guidance and specific reference for loess tunnels under different water content strata.